The Attitude of People in Anambra State, Nigeria towards COVID-19 Vaccination - Onyedinefu, Abraham; Nwankwo, Ignatius (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
This work investigated people's attitudes towards COVID-19 vaccination in the Anambra state, Nigeria. The 5C Model of Vaccination was adopted as the theoretical framework. The study adopted a mixed methods research design, using the multi-stage sampling procedure in selecting 378 respondents. A structured questionnaire and In-Depth Interview (IDI) guide served as instruments for data collection. The quantitative data were analysed using the Statistical Package for Social Sciences (SPSS) version 21, while the qualitative data were analysed using manual content analysis. One research hypothesis was formulated and tested using chi-square inferential statistics. The study found a negative attitude towards COVID-19 vaccination in Anambra state, Nigeria. The study recommended that the government, health workers, and NGOs work cooperatively to enlighten the public on the importance of accepting COVID-19 vaccination.